Design of Costas/PSK continuous wave LPI radar signal. Issue 3 (4th March 2017) - Yang, Hongbing; Chen, Jun
ABSTRACT: Low probability of intercept (LPI) radar signal design is a very important issue on modern battlefield. Different phase coding technologies are used to modulate Costas frequency hop sequence, and five kinds of continuous wave radar signals including Costas, Costas_qbarker, Costas_frank16, Costas_px16 and Costas_zadoff-chu13 are proposed and designed in this paper. The target resolution and LPI performance of the Costas and Costas/PSK continuous wave radar signals are analysed and compared. The ambiguity function and power spectral densities (PSDs) of five different kinds of signals are also simulated and studied. The results show that the target resolution and LPI performance of proposed Costas/PSK signal are better than Costas signal.